Membangun Konsep Urban Farming Di Wisata Umbul Helau Sebagai Bentuk Edukasi Kepada Masyarakat - Thabita Carolina; Susanti Sundari; Desy Rahmawati; Indah Purnama Sari (Jurnal Suara Pengabdian 45, 2022)
The PKM team with partners from Umbul Helau developed the concept of urban farming with aquaponics technology where hydroponic plant cultivation and integrated fish cultivation in the form of budikdamber. The activity purpose is to build the concept and introduce it to the community. The method used is ABCD (Asset Based Community Development), focusing on land assets owned by partners to be developed by building this urban farming activity. The stages are carried out starting from the time planning,, division of tasks, provision of materials, land preparation and cultivation of budikdamber media, seed distribution, control and evaluation. The results obtained are very encouraging where the plant has been harvested and with packaging that is sold and has economic value, catfish is growing and will harvest in the near future. In addition, education about this concept introduces to the elementary school (SD) students and teachers with a positive response.